Transitioning California's Adults: Providing 21st Century Education to Meet 21st Century Demands - Debra Jones; Marianne Fedele; Marian Thacher (Adult Education Research Conference, 2010)
For the first time in its history the United States is the only highly-developed democracy where the current generation of young adults is less likely to have completed high school than the previous generation. There are currently more than 12 million adults without a high school diploma in the workforce. In California one of every three students do not graduate from high school and four of five students enter the community college system unable to do college level work. Adult educators play a critical role in helping these students succeed and transition to further education and career opportunities.